Estudio comparativo de la organización de los medios informativos del cantón Babahoyo - Briones López, Margarita Mercedes (2023)
The internet is fertile ground for all types of audiences and digital media today are those that have gained greater reach, facilitating the exchange of information between online users and content creators, this study is based on the comparison between different digital media in the city of Babahoyo, among them are, the digital media MACO TV DIGITAL, CLICK NOTICIAS, BABAHOYO AL DÍA S.A.A., PORTAL INFORMATIVO DIGITAL, DIARIO ALDIA, in which the differences are made, with respect to the organization of the tasks of each of them, since they all have their own organizational structure, PORTAL INFORMATIVO DIGITAL, DIARIO ALDIA, in which the differences are made, with respect to the organization of the tasks of each of them, since they all have their own organizational structure. In order to carry out this research, the qualitative method and techniques such as the interview and the observation sheet were used. It is notorious the development of these media during the publication or transmission of some news, despite the fact that not all of them have a good organizational structure, they still perform the work within the media, dividing themselves into some areas. Many of them perform various activities, from being news editors to being reporters, however, despite this shortcoming, they are not affected. In addition, it was possible to analyze that not all media outlets have legal registration with Cordicom. Is concluded by recommending that digital media choose to have constant training in order to achieve greater development in the areas that are necessary, since journalists are often multifaceted.